Prospects and Problems on Internet Services Use Among the Faculty Members and Students of a Government-Subsidized University in Catanduanes - Tapado, Belen Molin (Journal of Technical Education and Training, 2016)
Technology is said to be a â€œgreat education equalizerâ€ since it gives teacher and learner access to enormous and almost boundless world knowledge using their schoolâ€™s desktop or laptop computers. Through the Internet, the Filipino students can learn at same level with students of more advanced institutions in highly industrialized countries in the world. This study employed the descriptive method research that utilized questionnaire to determine the prospects of internet and the problems on internet use of the respondents. Specifically, this study determined the level of knowledge and the degree of seriousness of the problems on internet use among the faculty members and students of the Catanduanes State University for school year 2015-2016. Result of the study showed that faculty members and students of the said government-subsidized university in Catanduanes have high level of knowledge on internet and have serious problem on internet use. There was significant relationship between the level of knowledge and degree of seriousness of the problems on internet use. The problem met is related to the gap of internet access or the supporting infrastructure available for both faculty and students. The internet services particularly at this institution should be rationalized and made available to all students anywhere in the campus. Awareness as to the benefits and convenience that can be offered by the Internet resources and services can ultimately be seen when efforts on changing attitudes of these sectors in higher institutional levels are to be focused together with the physical or technological architecture.